Pengembangan Sistem Kotak Amal Berbasis ESP32 Dan Sensor TCS3200 Untuk Monitoring Dan Analisis Donasi Real-Time - Andriyanti, Reza; Arbansyah, Arbansyah; Sumadi, Muhammad Taufiq (Forum Kerjasama Pendidikan Tinggi, 2025)
The development of a donation box system based on ESP32 and TCS3200 sensor aims to enhance the efficiency and transparency of donation management previously conducted manually. This system is designed to detect and classify banknote denominations, display donation status on an OLED LCD, and send notifications through a Telegram bot. Testing of the TCS3200 sensor revealed that the RGB value ranges for Indonesian Rupiah banknotes from Rp 1,000 to Rp 100,000 vary, with minimum and maximum values for each color component. For example, Rp 1,000 banknotes have a blue color range of 6-9, green 7-9, and red 7-9. The sensor can detect banknote denominations accurately despite some instability in readings influenced by lighting conditions and color interference. The OLED LCD successfully displays messages corresponding to system conditions, and notifications via the Telegram bot are received properly under stable network conditions. This system functions effectively, facilitating monitoring and enhancing transparency in donation management.